The effect of playing-based exercises on weight, body mass index, and fat percentage of overweight children with developmental coordination disorder - Maryam Shoja; Mohammad kazem Vaez mousavi; Abdollah Ghasemi (آموزش بهداشت و ارتقاء سلامت ایران, 2019)
Background and Objective: Body composition changes effects on physical, motor, and psychic aspects of people. The purpose of this study was to investigate the effect of playing-based exercises on weight, body mass index, and fat percentage of overweight children with developmental coordination disorder. Methods: The research method is semi experimental, with pre-test and post-test design. After checking health records, height and weight, and completing the questionnaire, from among the primary schools in district 15 of Tehran, 50 children, aged 8 to 10, were selected through targeted sampling method and based on entry criteria in 2015. After pre-test, they were randomly divided into two experimental groups (n=30) and control group (n=20). The experimental group participated in the protocol and received 3 sessions per week for 3 months. MABC-2 motor development test was used to measure the coordination of subjects and calipers and scales were used to combine the body. Data was analyzed using SPSS 21 and one-way covariance analysis at a significant level of 0.05. Results: Analysis of variables after 12 weeks of intervention indicated weight loss, fat percentage and body mass index in the experimental group and the intervention group received better scores compared to the control group and this difference was significant. Conclusion: Performing physical activity in the form of a game is one of the effective ways of intervening in children. Therefore, with early intervention, we can have a positive effect on the growth process and overweight.